A COMPARATIVE ANALYSIS OF WORKING SCHEDULE CASTE WOMEN AND OTHER WOMEN OF HARYANA ON THE BASIS OF LITERACY RATE - Kumari, Mona; Kumar, Satish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper represents the comparison between Scheduled Caste working Women and other Women of Haryana on the basis of literacy rate. The study is based on secondary data compiled from the Census of Haryana 2011. This paper in descriptive in nature. Data is processed with simple statistical techniques such as percentages and correlation. Correlation is calculated between literacy ratio and working population for SC Women and other Women populations. A comparison is also made to see if the literacy ratio and working population correlation exists for other Women and SC Women of Haryana. It is found in the study that there is a correlation between literacy rate and the working population of Women in Haryana. Fatehabad, Hisar, Sirsa, Jind and Bhiwani are the districts of Haryana where high percentage of Scheduled Caste Women are working whereas in Yamunanagar, Ambala, Nuh, Faridabad, Palwal less percentage of Scheduled Caste Women are working. If we see overall percentage working population of Women it is more in Bhiwani, Hisar, Jind, Mahendergarh, Rewari while it is low in Yamunanagar, Ambala, Faridabad, Nuh, Palwal. Surprisingly, percentage of working population for Scheduled Castes and overall, for women are high in Bhiwani, Jind and Hisar districts and low in Yamunanagar, Ambala, Faridabad, Nuh, Palwal districts of Haryana. In the last section of this paper, it is highlighted that by considering this fact that there is some relationship between literacy rate and percentage of working population, Government may formulate policies in consonance with this factor which is one of the important determinants of employment in our country.